The influence of material handling and operational performance on food loss occurrence in the milk supply chain - Dimas Auladi Yusuf; Fauzan Romadlon; Famila Dwi Winati (AGROINTEK, 2023)
Food loss occurs during production, handling, and post-harvest processing. Food loss also occurs because the product is under quality and shelf-life over. In addition, the performance and knowledge of farmers also need to be improved to minimize food loss. Food loss in the milk supply chain occurs due to spills, damage, and product contamination caused by operator negligence and poor handling procedures due to the lack of material handling and operational performance. This study aims to determine the effect of material handling and operational performance on food loss in the milk supply chain. The method used is a quantitative method with a statistical test Chi-Square. The results show that most material handling cases involve manual milking and milk storage. Another cause of food loss is the high production of bacteria, which impacts milk quality. In operational performance, the primary reason is communication among farmers regarding the cleanliness and handling of cattle during production. New farmers with low experience are expected to attend training to increase production capacity and avoid bacterial contamination. Upgrading Milking equipment is also essential to reduce food loss in the milk supply chain